2015
DOI: 10.1177/1475921715586625
|View full text |Cite
|
Sign up to set email alerts
|

The use of electromechanical impedance conductance signatures for detection of weak adhesive bonds of carbon fibre–reinforced polymer

Abstract: The joints between structural elements should ensure safe usage of the structure. One of the joining method is based on adhesive bonding. However, adhesive bonding has not replaced riveting yet. Rivets are still present even in newest composite aircraft AIRBUS 350. The reliability of the adhesive bonding limits the use of adhesive bonding for primary aircraft structures and there is a search for new non-destructive testing tools allowing to (1) assessment of the surfaces before bonding and (2) assessment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 11 publications
0
53
0
Order By: Relevance
“…It was proposed to embed the sensor into the lap joint [8,9]. The EMI method for CFRP adhesive bonds was investigated before in [10] but for moisture contamination, release agent contamination, and improper curing temperature of the adhesive. Only one sample of each kind was tested then.…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed to embed the sensor into the lap joint [8,9]. The EMI method for CFRP adhesive bonds was investigated before in [10] but for moisture contamination, release agent contamination, and improper curing temperature of the adhesive. Only one sample of each kind was tested then.…”
Section: Introductionmentioning
confidence: 99%
“…6 Later also the adhesive bonds were investigated with the EMI method. 9 High-frequency conductance curves in the range of the thickness resonance were studied. 7,8 The investigations were both numerical and experimental, but they focused only on aluminum lap joints.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 It was performed by embedding a transducer in the lap joint. 9 In the new research reported here, we present new prebond modifications (thermal treatment, de-icing fluid contamination, local precuring of the adhesive). Here we focus on the sensitivity of the EMI method to the adhesive bonds of CFRP composites.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Furthermore, many researchers have employed electromechanical impedance (EMI) technique; Malinowski1 et al used the frequency shift of the first resonant mode and the root mean square as indicators to differentiate strong bonds from weak bonds. [23] The authors detected a frequency change with weak bond level (contamination and level of poor curing). They used relative small specimens and the applicability of their proposed methodology is still debatable for realistic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Gulizzi et al [24] used EMI to monitor the degree of curing of the adhesive in aluminum joints on a larger scale in comparison to. [23] Because they used low frequencies, meaning relative long wavelengths, the efficiency of the technique to localise the weaken area is questionable. More recently, Dugnani et al proposed EMI technique by embedding piezoelectric transducers into the bondline.…”
Section: Introductionmentioning
confidence: 99%